Biomechanical analysis of fixation methods for acetabular fractures: A review. (March 2021) - Ferrante, Hannah; Schemitsch, Emil H.; Zdero, Radovan; Bagheri, Z. Shaghayegh
Highlights: This review paper summarizes the results of English language literature biomechanically focused on acetabular fracture fixation methods. It is necessary to standardized mechanical experimental method for biomechanical testing of the pelvis fracture. The effect of fracture micromotion for optimal stability and early healing in pelvis and acetabular fractures is unknown. More complicated acetabular fracture types that, such as posterior wall/posterior column complex fractures and transverse/posterior wall complex fractures, need to be addressed in a biomechanical research setting. Abstract: Acetabular fractures are known as one of the most frequent types of pelvic fractures with growing frequency among elderly people. Because of this, it is important to establish the methods of repair that will produce optimal outcomes for fracture healing and joint remobilization. Open reduction and internal fixation are considered as the "gold standard" of acetabular fracture repair; however, to the best of authors' knowledge, there is no systematic review comparing different repair methods from biomechanical point of view. As such, in this review paper, we summarize the results of English language literature biomechanically focused on acetabular fracture fixation methods in the last thirty years with the aim to create a reference for clinical decision making. The selected literature within the review is broken down into categories based on type of fracture, i.e., simple or complex, and then further grouped based on fracture line orientation. Clinical recommendations and future research possibilities are also provided.